Conifer proportion explains fine root biomass more than tree species diversity and site factors in major European forest types - Finér, Leena; Domisch, Timo; Dawud, Seid Muhie; Raulund-Rasmussen, Karsten; Vesterdal, Lars; Bouriaud, Olivier; Bruelheide, Helge; Jaroszewicz, Bogdan; Selvi, Federico; Valladares, Fernando (Elsevier, 2017)
Fine roots (diameter ≤2 mm) contribute significantly to the forest carbon cycle and are essential for resource acquisition from the soil. We conducted a study to assess the relationships between tree and ground vegetation fine root biomass and tree species diversity (monocultures compared to 2–5 species mixtures), conifer proportion and other site factors (stand basal area, soil carbon stocks and C:N ratio) in the six major European forest types, boreal forest in Finland, temperate forests in Poland, Germany and Romania, thermophilous deciduous forests in Italy, and Mediterranean forests in Spain. We sampled the fine roots of trees and ground vegetation to the depth of 20 cm in the mineral soil and allocated the fine root biomass to individual tree species using near-infrared reflectance spectroscopy (NIRS). We did not find any general positive effects of tree species diversity on the fine root biomass of trees or ground vegetation across the forest types and tree species combinations. However, our results suggest that tree fine root biomass increases with tree species diversity in pure broadleaf forests, but not in pure conifer forests. Species diversity explained 7% of the variation in tree fine root biomass in the broadleaf stands. The narrow tree species diversity gradient (1–2 species) in the conifer forests compared to the broadleaf forests (1−4) may have decreased the probability of conifer species combinations with below-ground functional traits conducive to over-yielding. Some evidence of diversity-mediated changes in the vertical rooting patterns of broadleaf trees and ground vegetation were found within the entire organic and 0–20 cm mineral soil layer although the weighted mean depth of fine root biomass was not affected. Negative diversity effects were found in the organic layer and positive diversity effects in the 0–10 cm mineral soil layer for broadleaf tree fine root biomass. Diversity effects were negative for ground vegetation fine root biomass in the 0–10 cm mineral soil layer. There was a general positive effect of conifer proportion on total fine root biomass in the organic layer, but not in the mineral soil layers. In general conifer proportion and site factors explained more of the variation in tree fine root biomass than tree species diversity. More research covering the annual variation in fine root biomass and deeper soil layers is needed before recommending managing species-rich forest for increasing below-ground biomass and carbon pools.
Keywords: carbon stock; fine root biomass; FunDivEUROPE; ground vegetation; soil C:N ratio; tree species richness; carbon; biomass; roots; vegetation